Correlation Between Thymus Radiology and Myasthenia Gravis in Clinical Practice - Luo, Huan; Xie, Shanshan; Ma, Chao; Zhang, Wenqiang; Tschöpe, Carsten; Fa, Xianen; Cheng, Jingliang; Cao, Jing (Frontiers in Neurology, 2019)
Background: The ability to distinguish between a normal thymus, thymic hyperplasia, and thymoma should aid in clinical management and decision making for patients with myasthenia gravis (MG). We sought to determine the accuracy of routine radiological examinations in predicting thymic pathology. Methods: We retrospectively analyzed the records of patients with MG who had undergone thymectomy from the Second Affiliated Hospital of Zhengzhou University. Each patient received at least one initial radiological diagnosis and one histological diagnosis, and the patients were classified into the all-patient, CT, contrast CT and MRI groups. The sensitivity, accuracy and specificity of each group were calculated for different histological types. Results: This study included 114 patients. All sensitivity, specificity and accuracy values except for sensitivity to hyperplasia in each group for different histological types were satisfactory. MRI had higher sensitivity (68.4%, 95% CI: 43.5-87.4%) to histological hyperplasia than did CT (14.3%, 95% CI: 0.4-57.9%) and contrast CT (26.7%, 95% CI: 7.8-55.1%). Contrast CT had higher specificity (97.9%, 95% CI: 88.9-99.95%) for histological hyperplasia than did MRI (88.5%, 95% CI: 69.9-97.6%). Discussion: For patients with MG, CT, contrast CT and MRI examinations can effectively identify thymoma. Additionally, compared with CT or contrast CT, MRI may have a stronger ability to distinguish thymoma and detect hyperplasia.